واقع التكنولوجيا المالية في الوطن العربي ودورها في تعزيز الشمول المالي (Journal of Economics and Management Research, 2023)
هدفت الدراسة إلى محاولة تشخيص واقع التكنولوجيا المالية في الوطن العربي، بإعتبارها بديلا مستحدثا للخدمات المالية، مع تحديد أهم العوائق والصعوبات التي تواجهها الدول العربية، وإبراز إمكانات التكنولوجيا المالية والفرص الممكن استغلالها. خلصت الدراسة إلى أنه بالرغم من تطور حجم الاستثمار في التكنولوجيات المالية في الدول العربية إلا أن دورها يظل في أغلب هذه الدول محدودا وضعيفا في تقليص فجوة الشمول المالي، ويرجع ذلك إلى تراكم عدة معوقات ترتبط بغياب القوانين والتعليمات المرتبطة بتراخيص الإنشاء وضعف رأس المال المخاطر ونقص الثقافة المالية الرقمية وعدم ملاءمة بيئة الأعمال لانطلاق هذه الشركات. The study aimed to attempt to diagnose the reality of Financial technology in the Arab world, As an innovative alternative to financial services, with the identification of most important obstacles and difficulties, and demonstrating the potential of Financial Technology and opportunities to be exploited. The study concluded that its role in most of these countries remains limited and weak in reducing the financial inclusion gap. This is due to the accumulation of several obstacles related to the absence of laws and instructions related to construction licenses, weak risk capital, lack of digital financial culture, and inadequate business environment for the launch of these companies.